Evaluation of the level of the competence development in the field of disease prevention and healthy lifestyle among medical students - N. V. Sivas (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
The principles of competent approach in the teaching of the medical university students in the disease prevention and healthy lifestyle are given in the article. For the formation of competence in the disease prevention and healthy lifestyles the pedagogical integral technology is used, developed by integrating content and disciplines of the medical education and Physical Culture. Further formation of competences in the preventive medicine and healthy lifestyle is being accomplished through the project method of teaching based on active projects. Advantages of the assessment of the competence of the medical university students in disease prevention and healthy lifestyle in the form of an authentic representational portfolio are given in the article. Modern assessment activity in education is focused on personal achievements of students, which may be reflected in different versions of portfolio. Authentic assessment is the most convenient and reliable in the case of the competence assessment, since it focuses primarily on the practical results of activity takes into account and promotes initiative, personal potential of the student, provides an opportunity to see the results and to obtain an assessment of achievements, allows not only to generate individual educational trajectory, but also to monitor the level of development of the educational content. The article reveals the content of the authentic representational portfolio and provides recommendations on its design and evaluation.